2011
DOI: 10.4104/pcrj.2011.00071
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunotherapy for the treatment of peanut allergy: systematic review of six case series studies

Abstract: Background: Allergy to peanuts is associated with considerable morbidity and, in a minority of cases, mortality. Natural resolution to peanut allergy occurs in only a few cases, hence the need to find effective interventions. Peanut oral immunotherapy (OIT) is a potentially important new therapeutic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 33 publications
0
38
0
1
Order By: Relevance
“…For example, in recent oral and sublingual immunotherapy trials, it is typical to administer doses on a daily basis and to escalate dosing over a period of 4-6 months (7,(24)(25). We had anticipated that a more rapid escalation and weekly dosing would be tolerated using this modified product, and although we do not know that a different approach to dosing would be beneficial, it is certainly possible that it would be.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in recent oral and sublingual immunotherapy trials, it is typical to administer doses on a daily basis and to escalate dosing over a period of 4-6 months (7,(24)(25). We had anticipated that a more rapid escalation and weekly dosing would be tolerated using this modified product, and although we do not know that a different approach to dosing would be beneficial, it is certainly possible that it would be.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment relies on strict dietary avoidance and ready access to injectable epinephrine. Traditional subcutaneous immunotherapy has proven unsafe for peanut allergy (5) and although oral and sublingual immunotherapy have shown some promise for peanut and other food allergens (6)(7)(8)(9), these approaches have the potential for significant adverse reactions (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The first studies of OIT for peanut allergy were uncontrolled and performed in the United States [56][57] and Europe, [58][59] and these studies showed promising results. A systematic review of OIT for peanut allergy by Sheikhet [60] discussed findings from these studies and 3 abstract articles. Most recently, 1 controlled study was performed in the United States and another uncontrolled one in Europe.…”
Section: Studies Of Oit For Peanut and Tree Nut Allergiesmentioning
confidence: 99%
“…En la última revisión sistemáti-ca de seis estudios publicada se concluye que para muchos pacientes esta inmunoterapia les permite incrementar el umbral de tolerancia durante el tratamiento, si bien las reacciones adversas fueron frecuentes durante la inmunoterapia, siendo la mayoría leves aunque algunas con riesgo vital. En conclusión, aunque parece ofrecer resultados prometedores, se recomienda realizar más estudios para demostrar la eficacia y coste-beneficio especialmente a largo plazo, debiéndose realizar estudios más potentes que permitan recomendar su uso clínico 47 . Por las limitaciones que hemos mencionado, se están explorando nuevas formas de administrar la inmunoterapia de forma que mejore su seguridad y eficacia.…”
Section: Aplicación Para El Tratamiento De Alergia Alimentariaunclassified